A Cross-Sectional Study of Clinical Practice for Midwifery Students with Design by Empathy during the Covid-19 Pandemic - Erina Windiany; Irma Sapriani; Tiarlin Lavida Rahel; Indah Yulika (Journal of Midwifery, 2023)
The learning activities of students in the clinical practice during the Covid-19 Pandemic are a challenge faced by health education institutions. The practical design is required for the implementation of safe clinical practice. In response, Budi Kemuliaan School of Health Science had designed the implementation of clinical practice learning with "design by empathy". This study aims to explore how clinical practice learning with "design by empathy" during the Covid-19 pandemic. A cross-sectional study was conducted on 62 students of the Midwifery Diploma Three Program, which were divided into two groups.Positive results were obtained from clinical practice learning with design by empathy during the pandemic which was seen from the presentation of students attendance, students health conditions, skills achievement, students and clinical instructor responses regarding the implementation of practical learning during the pandemic, and the acquisition of grades.